Определение доминирующего положения на рынке финансовых услуг - Усманов, А.С. (Культура народов Причерноморья, 2013)
В статье рассматриваются принципы и порядок определения доминирующего положения хозяйствующих субъектов на рынке финансовых услуг, разработанные в соответствии с Законом Республики Узбекистан « О конкуренции» и распространяются на отношения хозяйствующих субъектов, складывающиеся на рынке финансовых услуг. У статті розглядаються принципи і порядок визначення домінуючого положення господарюючих суб'єктів на ринку фінансових послуг, розроблені відповідно до Закону Республіки Узбекистан «Про конкуренцію» і поширюються на відносини господарюючих суб'єктів, що складаються на ринку фінансових послуг. During the various periods of transitional economy the various priorities in the policy of competition and antimonopoly regulation are placed in the forefront. Today in Uzbekistan the most priority task is the development of the competition and antimonopoly regulation in the markets of financial and, first of all, banking services. The markets of these services have a number of essential differences from the commodity markets, especially in defining a dominant position of economic entities. For this reason the given issue is also the subject of the present article. The article studies the principles and the order of defining a dominant position of economic entities in the financial service market developed according to the Law of the Republic of Uzbekistan “About the competition”. It covers the economic entities relations developing in the market of financial services.